Combining phenolic grafting and laccase-catalyzed cross-linking: Effects on structures, technofunctional properties and human immunoglobulin E binding capacity of egg white proteins. (1st September 2021) - Li, Mingqin; Karboune, Salwa; Liu, Lan; Light, Kelly; L'Hocine, Lamia; Achouri, Allaoua; Pitre, Mélanie; Mateo, Cesar
Highlights: Laccase-catalyzed cross-linking is an efficient approach for protein modification. Protein/ferulic acid (FA)-grafting enhances the protein cross-linking by laccase. Cross-linked products of lysozyme/ovalbumin can be modulated by attached FA sites. Polymerized lysozyme and oligomerized ovalbumin (n > 5) were obtained. Enhanced protein functionality and lower IgE binding were achieved. Abstract: The efficiency of laccase-catalyzed protein cross-linking can be impacted by substrate protein structure and competing reactions. In this study, chemical grafting of ferulic acid (FA) on protein surface was applied to modulate the cross-linking of two inflexible globular proteins, lysozyme (LZM) and ovalbumin (OVA). The extent of FA-grafting was positively correlated with protein cross-linking extent, and determined the molecular weight profile and structures of the cross-linked product. While laccase-catalyzed reactions (with or without free FA mediator) did not lead to evident cross-linking of the native proteins, oligomeric (up to 16.4%), polymeric (up to 30.6%) FA-LZMs and oligomeric FA-OVA (5.1–31.1%) were obtained upon the enzymatic treatments. The cross-linking on the grafted FA sites occurred mainly through the formation of 8–5′-noncyclic-dehydro-diferulic linkages. The effects of investigated cross-linking approach on the emulsifying, foaming properties and the immunoglobulin E (IgE) binding capacity of LZM and OVA were also evaluated in relation to the structural properties of cross-linked proteins.